2013
DOI: 10.1002/2013gl058136
|View full text |Cite
|
Sign up to set email alerts
|

IMF dependence of the azimuthal direction of earthward magnetotail fast flows

Abstract: Cluster magnetotail data together with ACE solar wind data from 2001 to 2009 are used to investigate the dependence of the azimuthal flow direction of earthward magnetotail fast flows on the interplanetary magnetic field (IMF). We find an indication that fast flows have favored azimuthal directions that have dependence on the IMF. Our results suggest that for positive IMF By, the favored azimuthal direction of the fast flows is dawnward in the northern plasma sheet and duskward in the southern plasma sheet. Fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

14
52
1

Year Published

2015
2015
2017
2017

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 22 publications
(67 citation statements)
references
References 38 publications
14
52
1
Order By: Relevance
“…Grocott et al, 2005). The azimuthal directions within the fast flow are also consistent with the statistical results of Pitkänen et al (2013) of IMF-dependent favourable azimuthal flow directions of convective fast flows, which they suggested possibly to be originated from untwisting.…”
Section: Discussionsupporting
confidence: 86%
See 4 more Smart Citations
“…Grocott et al, 2005). The azimuthal directions within the fast flow are also consistent with the statistical results of Pitkänen et al (2013) of IMF-dependent favourable azimuthal flow directions of convective fast flows, which they suggested possibly to be originated from untwisting.…”
Section: Discussionsupporting
confidence: 86%
“…Walsh et al (2009) suggested that the flow shear could be related to untwisting, but could not rule out a possibility of it to be related to internal flow patterns within the fast flow channel (depleted bubble), since the flow shear was observed only by one spacecraft. Besides these two studies, also Pitkänen et al (2013) have reported an indication of an azimuthal velocity shear across the neutral sheet during a fast flow in their fast flow example event. However, they showed only single satellite measurements and did not discuss the event any further.…”
Section: Introductionmentioning
confidence: 89%
See 3 more Smart Citations